Practical entity framework : database access for enterprise applications. - Gorman, Brian L. (APress, 2020)
Determine your object relational mapper (ORM) of choice for enterprise applications using .NET Framework, and especially .NET Framework Core 3.1 and higher. Real-world examples and considerations are presented in this book to help you create robust and efficient database solutions. Throughout the text, actual problems, questions, and common pitfalls are provided to help you recognize optimal solutions for maximum success in the different application scenarios you might encounter. Practical Entity Framework begins with a simple overview of the two most common approaches to working with databases--database first and code first--and then focuses on working in a code first manner. Taking the code first approach allows the entire database to be built and maintained in code so there is never a situation in which you cannot restore the database schema. Additionally, the code first approach creates an entirely transparent record of changes to the database that is easily tracked in source control. Emphasis throughout the book is on leaving you well positioned to architect and lead data development efforts for your organization. You will: Build robust and maintainable databases using a code first approach Create and execute stored procedures, triggers, and functions Analyze and optimize performance of database queries Ensure data integrity through keys, constraints, and relationships.